The Effect of Multiple Role Conflicts and Work Stress on the Performance of Female Employees - Irwan Usman; Fitriani Latief (Jurnal Economic Resource, 2022)
This study aims to determine the effect of multiple role conflicts and work stress on the performance of female employees at PT. Bank Syariah Indonesia Tbk, Pettarani Branch, Makassar City. The population in this study was female employees at PT. Bank Syariah Indonesia Tbk Pettarani Branch, totaling 30 employees. The sampling technique is saturated sampling, where all population members are used as samples. This quantitative research uses primary data from the results of filling out questionnaires by respondents. The analytical method used is the classical assumption test, multiple linear regression, t-test, and partial test. The results showed that both partially and simultaneously, the multiple role conflict and job stress variables negatively and significantly affected the performance of female employees at PT. Bank Syariah Indonesia Tbk, Pettarani Branch.